2010
DOI: 10.1021/ac102338n
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fingerprinting of Biofluids by Infrared Spectroscopy: Modeling and Optimization of Flow Rates for Laminar Fluid Diffusion Interface Sample Preconditioning

Abstract: The laminar fluid diffusion interface (LFDI) is a microfluidic tool that manipulates the composition of liquid mixtures by exploiting differences among diffusion coefficients of the dissolved components. One application is the preprocessing of (bio)fluids prior to spectroscopic characterization. For example, in the case of infrared (IR) spectroscopy, the technique can improve sensitivity to low-concentration serum metabolites. The practical benefit is “metabolic fingerprinting” measurements that are more sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Consequently, the method assisted the sequestering and quantifying of serum creatinine in a range of 0.7-16 mg/dL from high concentrated molecules like protein. 33,287,288 Another strategy was employed to determine and quantify the lipidomic profile by eliminating the proteins in the serum and pre-concentrating only the non-polar analytes using solvent extraction. The study has demonstrated an improvement in the predictions of levels of cholesterol and triglycerides compared to direct ATR analysis on serum.…”
Section: Ir Spectroscopy For Detection Of Selected Analytesmentioning
confidence: 99%
“…Consequently, the method assisted the sequestering and quantifying of serum creatinine in a range of 0.7-16 mg/dL from high concentrated molecules like protein. 33,287,288 Another strategy was employed to determine and quantify the lipidomic profile by eliminating the proteins in the serum and pre-concentrating only the non-polar analytes using solvent extraction. The study has demonstrated an improvement in the predictions of levels of cholesterol and triglycerides compared to direct ATR analysis on serum.…”
Section: Ir Spectroscopy For Detection Of Selected Analytesmentioning
confidence: 99%
“…50,100 Some other techniques, such as electrochemical array detection, Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy, have also become increasingly used for metabolomics. 101,102 The choice of analytical platform may remain greatly dependent on the biological questions and the samples that require analysis (in terms of both nature and number). Many existing platforms combine both NMR and MS, which are described as complementary and synergetic tools.…”
Section: ■ Analytical Platformsmentioning
confidence: 99%
“…The resultant infrared absorbance spectrum is characteristic of the functional groups within the sample and thus constitutes an unique fingerprint [39]. This is a promising analytical tool for metabolomic studies however, it is important to note that the presence of water in a sample may influence the bands at certain specific wave number and that environmental conditions around the FT--IR instrument can cause variations in the spectra.…”
Section: Technological Approachesmentioning
confidence: 99%